Contemporary Interpretation of the Religion Clauses: The Church and Caesar Engaged in Conversation - Araujo, Robert John (Journal of law and religion, 1993)
In the contemporary age, when we hear references to the First Amendment religion clauses, we may think of cases in which courts have addressed the legality of prayers in schools, the displays of religious symbols during the holiday seasons, or monetary and other tangible assistance provided by governments to parochial schools. Just this past semester, the United States Supreme Court addressed the question of animal sacrifice occuring in a religious ritual as protected conduct under the free exercise of religion clause. Important as these issues are, they are not the subject of this investigation. My proposal is to address the First Amendment religion clauses in a different context. The goal is to show that it is both Constitutionally permissible and helpful (and quite possibly essential) to American republican democracy that the church (and individuals holding religious beliefs) (can and ought to) participate in the public discourse involving a wide variety of political and social issues with which our local, state, and national communities are concerned.